SUMBER DAYA MANUSIA (APARATUR PEMERINTAH DAERAH) DALAM PELAYANAN PUBLIK - Wairocana, Gst. Ngurah (PIRAMIDA, 2012)
The aim of this paper which is entitled ? Behavior Norm of States Apparatus in Establishing Good Governance?, is to analyze behavior of states apparatus in providing public service. The approach applied is functional approach, i.e an approach in administration law which view functioning of states apparatus in public service through two core measurements, that are 1) serving attitude (dientsbaarheid-servitut), 2) reliability (betrouwbaarheid reliability), which is consist of openness (openheid); carefulness (naugeztheid); integrity (integriteit); simplicity (soberheid); and honor/honesty (eerlijkheid-honesty). Measuring rod used is community report related to maladministration of regional states apparatus to the national Ombudsman Commission. Additionally, interviews with community members which have made an application for identity card, birth certificate, marriage certificate, and the like, have done as supporting information. The finding shows that so far, community members state that services provide by states apparatus is sufficient.
Keywords: good governance, public service, maladministration